2015
DOI: 10.1080/15384101.2015.1064207
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-410 targeting the cyclin B1 gene plays a role in pituitary gonadotroph tumors

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that act as posttranscriptional regulators of gene expression, and are frequently altered in human neoplasias. Here, we have analyzed the miRNA expression profile of human gonadotroph adenomas versus normal pituitary tissue using a miRNACHIP microarray. We demonstrate that miRNA-410 is downregulated in gonadotroph adenomas when compared with normal pituitary gland. We validate CCNB1 as target of miRNA-410 since its overexpression reduces CCNB1 at protein and mRNA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 36 publications
1
40
0
2
Order By: Relevance
“…For examples, miR-410 is downregulated in pituitaty gonadotroph tumors and suppresses cell proliferation by targeting CCNB1 [21]. MiR-410 inhibits cell growth, migration and invasion as well as the G1/S cell-cycle arrest through the downregulation of angiotensin II type 1 receptor in pancreatic cancer, functioning as a tumor suppressor [22].…”
Section: Discussionmentioning
confidence: 99%
“…For examples, miR-410 is downregulated in pituitaty gonadotroph tumors and suppresses cell proliferation by targeting CCNB1 [21]. MiR-410 inhibits cell growth, migration and invasion as well as the G1/S cell-cycle arrest through the downregulation of angiotensin II type 1 receptor in pancreatic cancer, functioning as a tumor suppressor [22].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, miR-410-3p and miR-497-5p have also been reported to act as tumor suppressors in several different cancers. Decreased miR-410 expression levels have been reported in pituitary gonadotroph tumors, pancreatic tumors, and gastric tumors by targeting cyclin B1 (CCNB1) [33], angiotensin II type 1 receptor (AGTR1) [34], and MDM2 proto-oncogene (MDM2) [35], respectively. Overexpression of miR-410 in these tumor cells suppressed tumor proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…24 is a target of miR-199a-5p in mouse keratinocytes. 34 Khan et al reported that miR-379 regulates cyclin B1 expression and is decreased in breast cancer. 34 Khan et al reported that miR-379 regulates cyclin B1 expression and is decreased in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 It is estimated that miRNAs regulate more than 30% of human protein-coding genes, demonstrating the essential role of miRNAs in modulating gene expression. 31,32 Several studies have shown that miR-199a-5p, 33 miR-410 34 and miR-379 35 mediate the cell cycle by directly regulating cyclin B1 (Ccnb1) expression in several cell types of cells.…”
Section: Introductionmentioning
confidence: 99%